A newer and broader definition of burnout: Validation of the "Burnout Clinical Subtype Questionnaire (BCSQ-36)" - García-Campayo Javier; Montero-Marín Jesús (BMC, 2010)
Abstract Background Burnout syndrome has been clinically characterised by a series of three subtypes: frenetic, underchallenged and worn-out, with reference to coping strategies for stress and frustration at work with different degrees of dedication. The aims of the study are to present an operating definition of these subtypes in order to assess their reliability and convergent validity with respect to a standard burnout criterion and to examine differences with regard to sex and the temporary nature of work contracts. Method An exploratory factor analysis was performed by the main component method on a range of items devised by experts. The sample was composed of 409 employees of the University of Zaragoza, Spain. The reliability of the scales was assessed with Cronbach's α, convergent validity in relation to the Maslach Burnout Inventory with Pearson's r, and differences with Student's t-test and the Mann-Whitney U test. Results The factorial validity and reliability of the scales were good. The subtypes presented relations of differing degrees with the criterion dimensions, which were greater when dedication to work was lower. The frenetic profile presented fewer relations with the criterion dimensions while the worn-out profile presented relations of the greatest magnitude. Sex was not influential in establishing differences. However, the temporary nature of work contracts was found to have an effect: temporary employees exhibited higher scores in the frenetic profile (p < 0.001), while permanent employees did so in the underchallenged (p = 0.018) and worn-out (p < 0.001) profiles. Conclusions The classical Maslach description of burnout does not include the frenetic profile; therefore, these patients are not recognised. The developed questionnaire may be a useful tool for the design and appraisal of specific preventive and treatment approaches based on the type of burnout experienced.